Makna Keharmonisan keluarga dalam Perspektif Kolose 3:18-21 (International Forum of Researchers and Lecturers, 2025)
In modern society, many families face challenges such as conflict and divorce, so an understanding of healthy family relationships is becoming increasingly relevant. The purpose of this study is to explore the meaning of family harmony in the perspective of Colossians, as well as how this teaching can be applied in everyday life. The methodology used is a descriptive qualitative approach with an analysis of the scriptural text, specifically Colossians 3:18-21, to draw the theological meaning of Paul's teaching on roles and responsibilities in the family. The main results of the study show that family harmony is characterized by love, mutual respect, and obedience in a spiritual context. Emphasis on the reciprocal relationship between husband and wife, as well as positive parenting between parents and children, is key to creating a healthy family environment. In conclusion, applying the values found in Colossians can help families face the challenges of modern times and create more harmonious and equitable relationships.